Exploring the Role of Social Visibility and Goal Framing in PWYW Pricing - Roy, Rajat; Sharma, Piyush; Rabbanee, Fazlul (Association for Consumer Research Asia-Pacific, 2015)
Pay what you want (PWYW) is an innovative participative pricing mechanism that allows consumers to pay any price (including zero) for a product or service. We contribute to the growing literature on PWYW pricing by showing that consumers’ price consciousness moderates the effects of altruism and internal reference price on their willingness to pay (WTP). Moreover, social visibility (private vs. public) moderates the impact of consumer goals (intrinsic vs. extrinsic) on WTP and this interaction disappears in the presence of an external reference price.